KARAKTERISTIK DAN MUTU TEH BUNGA LOTUS (Nelumbo nucifera) - Ria Kusumaningrum; Agus Supriadi; Siti Hanggita R.J (Universitas Sriwijaya, 2013)
The objective of this research was to determine the characteristics and quality of lotus flower tea. The research was designed as Factorial Completely Randomized designed with two factors and three replicates. The first factor was the process method (with and without enzymatic oxidation) and the second factor was withering time (8 and 10 hours). There parameters were the water content, ash content, antioxidant activity and tannin content, colour measurement, yield measurement and hedonic quality test by tea taster inclue ALI (appearance, liquor and infusion leaf). The best result were showed in the O0T1 treatment with water content 9.65%, antioxidant activity 32.19%, tannin 152.73ppm, lightness 48.63%, chroma 7.36%, hue 69.77% dan yield 25.88%. The best result of analysis quality and sensory showed in the O1T1 treatment with score 47 and medium quality.